PREMARITAL COUNSELING; MODEL KONSELING PRA NIKAH MEMBENTUK KELUARGA SAKINAH, MAWADDAH, WA RAHMAH - Muallifah, Muallifah; Sa'diyah, Elok Halimatus; Muhayani, Ulfah (EGALITA, 2023)
Every married couple definitely wants a harmonious, happy and sakinah, mawaddah and rahmah household. The quality of marriage that achieves harmony and happiness has an impact on the psychological well-being of children, the optimal development of children's potential and the achievement of a sakinah household. Conversely, when the family is not harmonious, it can lead to divorce, and the psychological condition of the child is shaken. This study aims to determine the model of premarital counselling given to prospective bridal couples. This study used a qualitative method with a phenomenological approach which was carried out on several KUA marriage assistant counsellors. Data collection techniques were carried out through interviews and FGD (focus group discussion). Stages of data analysis through; (1) The researcher begins by thoroughly describing his experience, (2) grouping the data into meaningful units, the researcher details and writes a textual description of his experience, (3) reflects on his thoughts and uses imaginative variations (imaginative variation), (4) construct all explanations about the meaning and essence of the subject's experience. The research results obtained: (1). Premarital Counseling (premarital counselling) is an obligation for prospective married couples, (2) the need for the implementation of Premarital Counseling to be carried out intensively to increase happiness, (3) premarital counselling as an alternative step to minimize Divorce rates and Preventive Marriage Problems.